THE ASSESSMENT OF NATIONAL ROAD SURFACE CONDITIONS ANALYSIS BASED ON THE INTERNATIONAL ROUGHNESS INDEX (IRI) METHOD USING ROADROID APPLICATION - Mahendra, Didi Herianto; Erwan, Komala; Kadarini, Siti Nurlaily (Fakultas Teknik Universitas Tanjungpura, 2023)
Road infrastructure is built as an infrastructure to meet needs and facilitate accessibility and mobility of socio-economic activities in the community. With the benefits that are so important, therefore the road construction and maintenance sector become a priority to be researched and developed in planning, implementing, and maintaining it. At the location of Jalan Khatulistiwa section, most of the road surface conditions are in moderate condition so the recommendation for improving road surface conditions is periodic maintenance on 56 segments and the other 13 segments are carried out routine maintenance. In the IRI measurement using the Roadroid application, there is a tendency to produce an IRI value that is greater than the IRI measurement using a laser profilometer, but the IRI value obtained by Roadroid tends to approach the IRI value as measured by a laser profilometer with an average percentage difference per segment of 2.91% with 2 segments that have different conditions. Based on the provisions of Pd-01-2021-BM, the IRI value test of the Roadroid has met the requirements as a class III measure of unevenness (IRI).